The antiproliferative activity of Sclerotia of Lignosus rhinocerus (Tiger Milk Mushroom) - Lee, M.L.; Tan, N.H.; Fung, S.Y.; Tan, C.S.; Ng, S.T. (Hindawi, 2012)
Lignosus rhinocerus, the tiger milk mushroom, is one of the most important medicinal mushrooms used by the indigenous people of Southeast Asia and China. It has been used to treat breast cancer. A cold water extract (LR-CW) prepared from the sclerotia of L. rhinocerus cultivar was found to exhibit antiproliferative activity against human breast carcinoma (MCF-7) and human lung carcinoma (A549), with of 96.7 μg/mL and 466.7 μg/mL, respectively. In comparison, LR-CW did not show significant cytotoxicity against the two corresponding human normal cells, 184B5 (human breast cell) and NL 20 (human lung cell). DNA fragmentation studies suggested that the cytotoxic action of LR-CW against cancer cells is mediated by apoptosis. Sephadex G-50 gel filtration fractionation of LR-CW yielded a high-molecular-weight and a low-molecular-weight fraction. The high-molecular-weight fraction contains mainly carbohydrate (68.7%) and small amount of protein (3.6%), whereas the low-molecular-weight fraction contains 31% carbohydrate and was devoid of protein. Only the high-molecular-weight fraction exhibited antiproliferative activity against cancer cells, with of 70.0 μg/mL and 76.7 μg/mL, respectively. Thus, the cytotoxic action of the LR-CW is due to the high-molecular-weight fraction, either the proteins or protein-carbohydrate complex.